Different types of low back pain in relation to pre- and post-natal maternal depressive symptoms - Gong Long; Zhang Yao Yao; Yang Na; Yi Ping; Sun Wei; Tan Mingsheng (BMC, 2020)
Abstract Background Low back pain (LBP) is a common musculoskeletal problem during pregnancy, with an estimated prevalence ranging from 30-78% (Mota MJ et al. J Back Musculoskelet Rehabil 28(2):351-7,2015 and Abebe E et al. J Med Sc Tech 3(3). 37-44,2014). Women reporting LBP are at increased risk of developing perinatal depression. Pregnancy-related LBP is highly heterogeneous and can be divided into lumbar pain (LP), posterior pelvic pain (PPP), and combined pain (CP). Therefore, the purpose of this study was to investigate the associations between LBP and perinatal depressive symptoms. Methods This was a retrospective case-control study conducted from January 2016 to April 2019. A total of 484 pregnant women were enrolled in this study: a case group of 242 pregnant women who were diagnosed with LBP and an age-matched control group of 242 pregnant women without LBP. The Edinburgh Postnatal Depression Scale (EPDS), LBP characteristics, and questionnaires about pregnancy that included demographic, parity, work, comorbidity, and previous pregnancy data were completed and compared between the case group and the control group. Results A total of 68 of 242 (28.1%) women experienced PPP, 142 (58.7%) had lumbar pain(LP), and 32 (13.2%) had combined pain. Furthermore, 26.5% of women with prenatal depression in the LP subgroup remained depressed 6 months postnatally, while the percentages for women in the PPP subgroup and CP subgroup were just 10.6% and 15.6%, respectively. The percentage of women who recovered anytime between delivery and six months postnatally in the PPP subgroup was significantly higher than that in the LP subgroup (31.7% vs. 14.7%, P < 0.001). Conclusions There is a difference in the prevalence of prenatal, postnatal, and perinatal depressive symptoms among pregnant women with different types of LBP. It is necessary to screen prenatal and postnatal depression separately and differentiate the types of LBP during pregnancy. Attention to these factors may help to outline better management strategies to improve maternal health.